An evaluation of erosion in cuesta relief: São Paulo State, Brazil - Stefanuto, Estêvão Botura [UNESP]; Lupinacci, Cenira Maria [UNESP]; Carvalho, Filipe; Francos, Marcos; Úbeda, Xavier (Elsevier, 2022)
Cuestas are relief features whose evolution has traditionally been attributed to erosion processes. They are habitually studied in many regions of the world. In Brazil, however, studies of erosion processes in cuestas are uncommon, despite the presence of this type of relief in several parts of the country. The aim of this study was to identify relevant correlations between local geographical conditions and physical-hydrological properties of the soil, and to identify the prevailing factors in the development of rill erosion, ravines and gullies in cuestas. We analyze various physical properties of the soil, including grain size, resistance to penetration, permeability and infiltration rates. The geographic variable slope was also considered. The data variables were processed using geostatistical techniques (ordinary kriging) and statistics (factor analysis). The results show that data referring to grain size, soil resistance to penetration and infiltration present statistically significant differences and can be used to assess the spatial distribution of erosion landforms. Details of the behavior of clays and the transitions between the clayey and sandy sector also helped to understand the location of erosion landforms. The steep morphology of the cuestas, associated with the presence of lithologies of varying resistance, generates different soil types, even in small catchments. These differentiations contribute to the development of erosion features and generate gullies covering large areas and whose evolution is difficult to explain. Thus, the study of erosion in cuesta lands is necessary and should be expanded in Brazil. The methodology used in this study has the potential to be applied to other catchments, and can thus contribut to the study of erosion processes in cuestas.
Keywords: Brazil; Cuesta relief; Geostatistical analysis; Soil erosion